How automatic speech recognition can assist children with dyslexia in literacy skills - Husni, Husniza (2007)
This paper gives an extensive review of various studies on automatic speech recognition (ASR) technology used to facilitate people with dyslexia in acquiring basic literacy skills.The paper delineates how the technology can help children to improve their abilities in reading, spelling, and writing.These basic skills require a person to be aware of the phonological aspect of a language. Unfortunately, phonological awareness is a major problem for people with dyslexia. Therefore, ASR technology is seen to have enhanced their phonological awareness ability by providing multi-sensory experience and thus improves the essential skills needed in education.This paper also outlines a few problems of using current available ASR tools to cater for the needs of dyslexic children to improve their academic performances.